Recognition of prior learning at the centre of a national strategy: tensions between professional gains and personal development - Lima, Licínio C. (2016)
This paper focuses on recognition of prior learning as part of a national policy based on European Union guidelines for lifelong learning, and it explains how recognition of prior learning has been perceived since it was implemented in Portugal in 2000. Data discussed are the result of a mixed method research project that surveyed adult learners, some of whom were interviewed, who successfully completed the recognition of prior learning process from 2007 to 2011 in a new opportunities centre. Adult educators, and workplace representatives from the companies in which these adults in the recognition of prior learning process were working, were also part of the survey. A theme-based content analysis was done on the resulting data. Findings revealed tension between the goals of economic and human resource management and the change experienced by these adult learners in their professional status. Based on these results, the closing remarks to this article highlight the tensions caused by the failure of the goals of the policy to which recognition of prior learning was central, and the personal and social changes referred to by learners. Important educational changes were achieved although they were undermined by the adult education policy and European Union guidelines.